2016
DOI: 10.1080/01612840.2016.1181125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dosage and Type of Music Therapy in Symptom Management and Rehabilitation for Individuals with Schizophrenia

Abstract: The purpose of this systematic review was to investigate the influence of dosage, type (active, receptive, or combined), and format (individual or group) of music therapy for individuals with schizophrenia. With the terms "music*" and "schizophreni*," six research databases were searched: CINAHL, EMBASE, Music Index, PsycInfo, Pubmed, and RILM. The search was limited to studies written in English, peer-reviewed, and published between 1991 and 2015. Seventeen articles met the stated criteria. Dosage of music th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…That review showed that three types of music therapy did not show differences in the alleviation of anxiety symptoms. This difference might result from the total intervention time, which was 2,880 min in our study; the longest music therapy time examined by Chung and Woods‐Giscombe () was 540 min. Thus, music therapy might have a dose–response relationship (Gold et al .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…That review showed that three types of music therapy did not show differences in the alleviation of anxiety symptoms. This difference might result from the total intervention time, which was 2,880 min in our study; the longest music therapy time examined by Chung and Woods‐Giscombe () was 540 min. Thus, music therapy might have a dose–response relationship (Gold et al .…”
Section: Discussionmentioning
confidence: 64%
“…The diversion principle is an effective strategy for transferring emotions about the disease that are deeply trapped and for relieving anxiety through immersion in music (Shih & Hwang ). Chung and Woods‐Giscombe () performed a systematic review to investigate the effect of music therapy on anxiety in patients with schizophrenia. That review showed that three types of music therapy did not show differences in the alleviation of anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ίσως, μάλιστα, να θυμίζει το κύμβαλον αλαλάζον από την επιστολή του Αποστόλου Παύλου, ΠΡΟΣ ΚΟΡΙΝΘΙΟΥΣ. 33 Συνολικά, η απαρίθμηση όλων αυτών των διαβλητών στοιχείων συμπεριφοράς υπήρξε μάλλον διακριτική, χωρίς να διακρίνεται από ακραία στηλίτευση. Την έντονα απορριπτική του διάθεση ο συντάκτης την αποκαλύπτει αμέσως στη συνέχεια, όταν σημειώνει ότι ο ίδιος δε θα ζητούσε βοήθεια από τέτοιους γιατρούς (13.7-9).…”
Section: παράγραφος 13unclassified
“…2,6,18,19,36,44),  ανάγκη ταχείας περίθαλψης (παρ. 2,25,30,33,34,43),  διακριτική ευχέρεια του γιατρού να αναλάβει ή όχι ένα περιστατικό που είναι σοβαρό και αμφίβολης έκβασης (παρ. 12),  ο ασθενής μπορεί να συνεχίσει μόνος του τη θεραπεία και να προσφέρει στον εαυτό του ό,τι τον ωφελεί (παρ.…”
Section: β 2 4 3 περι των εντος παθωνunclassified
See 1 more Smart Citation